Optical wireless communications : system and channel modelling with MATLAB - Ghassemlooy, Zabih; Popoola, W.; Rajbhandari, S. (Boca Raton, FL : CRC Press, 2013)
"Incorporating MATLAB, this book provides a single resource for optical wireless communication systems based on the systems approach. It presents past and current research activities to illustrate optical sources, transmitters, detectors, and receivers used in optical wireless communications. The text covers both indoor and outdoor environments as well as how different factors, including various channel models, affect the system performance. The authors also discuss the emerging field of visible light communications and describe techniques for mitigating channel impact on the system performance using theoretical analysis and simulation. Other topics include hybrid optical and RF wireless systems"--
Introduction: Optical Wireless Communication Systems Wireless Access Schemes A Brief History of OWC OWC/Radio Comparison Link Configuration OWC Application Areas Safety and Regulations OWC Challenges Optical Sources and Detectors Light Sources Light-Emitting Diode The Laser Photodetectors Photodetection Techniques Photodetection Noise Optical Detection Statistics Channel Modelling Indoor Optical Wireless Communication Channel Artificial Light Interference Outdoor Channel Modulation Techniques Introduction Analogue Intensity Modulation Digital Baseband Modulation Techniques Pulse Position Modulation Pulse Interval Modulation Dual-Header PIM Multi-Level DPIM Comparisons of Baseband Modulation Schemes Subcarrier Intensity Modulation Orthogonal Frequency Division Multiplexing Optical Polarization Shift Keying Appendices System Performance Analysis: Indoor Effect of Ambient Light Sources on Indoor OWC Link Performance Effect of FLI without Electrical High-Pass Filtering Effect of Baseline Wander without FLI Effect of FLI with Electrical High-Pass Filtering Wavelet Analysis Link Performance for Multi-path Propagation Mitigation Techniques Equalization as a Classification Problem Introduction to Artificial Neural Network Training Network The ANN-Based Adaptive Equalizer FSO Link Performance under the Effect of Atmospheric Turbulence On-Off Keying Pulse Position Modulation Subcarrier Intensity Modulation Atmospheric Turbulence-Induced Penalty Appendices Outdoor OWC Links with Diversity Techniques Atmospheric Turbulence Mitigation Techniques Receiver Diversity in Log-Normal Atmospheric Channels Transmitter Diversity in a Log-Normal Atmospheric Channel Transmitter-Receiver Diversity in a Log-Normal Atmospheric Channel Results and Discussions of SIM-FSO with Spatial Diversity in a Log-Normal Atmospheric Channel SIM-FSO with Receiver Diversity in Gamma-Gamma and Negative Exponential Atmospheric Channels Terrestrial Free Space Optical Links with Subcarrier Time Diversity Aperture Averaging Appendices Visible Light Communications Introduction System Description System Implementations Multiple-Input-Multiple-Output VLC Home Access Network References
Includes bibliographical references and index.
Keywords: MATLAB; Optical communications; Signal processing; Free space optical interconnects; Signals and signaling -- Mathematical models